2018
DOI: 10.5964/ejop.v14i4.1553
|View full text |Cite
|
Sign up to set email alerts
|

Family acculturation in host and immigrant couples: Dyadic research in an Italian context

Abstract: The purpose of this research is to study acculturation strategies and attitudes in central and peripheral domains of host and immigrant couples in an Italian context. The participants were 60 dyads (30 host couples and 30 immigrant couples) who completed a questionnaire based on the Relative Acculturation Extended Model (RAEM). Based on the analysis, we found that the general acculturation attitude preferred by immigrant couples is integration, and Italian couples prefer that immigrants adopt it. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…No prior study could be found seeking to benefit from this. Italy was the primary target for collection of data because migrants represent around 9% of the Italian population, and tend to opt for an integrative cultural orientation [ 22 ]. In fact, intermarriages including one native represent around 10% of its total marriages [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…No prior study could be found seeking to benefit from this. Italy was the primary target for collection of data because migrants represent around 9% of the Italian population, and tend to opt for an integrative cultural orientation [ 22 ]. In fact, intermarriages including one native represent around 10% of its total marriages [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In cross-cultural psychology-the discipline informing this study and most of the literature reviewed here-acculturation refers to changes in language, identity, values, and behaviors resulting from living in a new cultural environment (Berry 2006;Schwartz et al 2010). Even though migrant couples typically largely agree on the acculturation strategies they should adopt (Rania, Migliorini and Rebora 2018), discrepancies exist in how partners respectively experience settlement in the new country and in how they individually adapt to it. These discrepancies, or post-immigration gaps, can play a key role in couples' postimmigration adaptation, especially when they are related to gender role values (Grzywacz et al 2009;Cruz et al 2014;Accordini, Giuliani and Gennari 2018) or motivation and acculturation (Ben-David and Lave´e 1994;Kisselev, Brown and Brown 2010;Kanat-Maymon et al 2016).…”
Section: Immigration and Couple Relationshipsmentioning
confidence: 99%
“…Referring, therefore, to this corpus of literature, we believe that the concept of "doing family" can be extended to those refugee families who face a non-regular life path with atypical developments compared to those who remain in their home-country. In fact, in the literature, migrant families have been studied as they adapt to their new context: this implies a redefinition of roles and parenting competences as well as a rethinking of daily routines and symbolic meanings attributed to rituals experienced in contexts distant from where the migrants were born (Migliorini et al, 2016;Rania et al, 2015;Rania et al, 2018aRania et al, , 2018bRania et al, 2019;Strasser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%